Determination of the effects of size and sex on the diet of the green tiger prawn, Penaeus semisulcatus (de Haan) from Capiz and Pilar Bays, Northern Panay Island. - Nabuab, Fenelyn Montales (2003.)
In this study, the natural diet of Penaeus semisulcatus (de Haan) or green tiger prawn was described. Green tiger prawns were collected from Capiz-Pilar Bays using municipal trawls. The dietary components of 30 male (100-199.99 mm TL) and 65 female (110-249.99 mm TL) was determined by stomach content analysis using numerical composition and frequency of occurence (FOC) of food items. The results revealed eight major food items: unidentified matter, shrimps, diatoms, bivalves, gastropods, forams, polychaetes, and others. Of these major dietary composition, shrimps, bivalves, gastropods, forams, unidentified matter and others were common to both male and female. Food items with FOC of less than 2% were lumped into others. Based on the results, there was no significant difference in the dietary composition of male and female prawns. Development shift in the diet of the male P. semisulcatus occurs as the prawns increase in size due to enhancement of mobility and increase in chela size and jaw gape. There is no clear trend in the change in the diet of female P. semisulcatus. It is probable that the structural modifications in female prawns are not as significant as in males to cause variation in their diet.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Green Tiger Prawn -- Capiz